The impact of DICTs on Chemistry teaching and learning: A systematic Review (Research, Society and Development, 2025)
This article aims to analyze, through a Systematic Literature Review (SLR), the impact of Digital Information and Communication Technologies (DICTs) on the teaching and learning of Chemistry, identifying their pedagogical contributions, methodological trends, and possible limitations. The research was developed based on articles published between 2019 and 2025, selected from national and international databases, such as the CAPES Platform, Scopus, Google Scholar, and institutional repositories, considering criteria of relevance, quality, and timeliness. The results show that the use of DICTs has significantly contributed to making Chemistry teaching more dynamic, interactive, and contextualized, facilitating the understanding of abstract concepts and promoting more meaningful learning. However, the analysis also points to important challenges, such as the need for teacher training focused on the pedagogical use of technologies and inequalities in access to digital resources. In conclusion, when used in a planned and integrated manner with traditional practices, ICTs enhance student protagonism and the construction of scientific knowledge, constituting essential tools for innovative chemistry teaching aligned with the demands of contemporary society.